An equilibrium model of habitat conservation under uncertainty and irreversibility - Luca Di Corato; Michele Moretto; Sergio Vergalli (Fondazione Eni Enrico Mattei (FEEM), 2010)
In this paper stochastic dynamic programming is used to investigate habitat conservation by a multitude of landholders under uncertainty about the value of environmental services and irreversible development. We study land conversion under competition on the market for agricultural products when voluntary and mandatory measures are combined by the Government to induce adequate participation in a conservation plan. We analytically determine the impact of uncertainty and optimal policy conversion dynamics and discuss different policy scenarios on the basis of the relative long-run expected rate of deforestation. Finally, some numerical simulations are provided to illustrate our findings.
Keywords: C61; D81; Q24; Q58; 330; Optimal Stopping; Deforestation; Payments For Environmental Services; Natural